IMPACT OF PHARMACIST-LED DIABETES EDUCATION ON PATIENTS’ ACHIEVEMENT ACCORDING TO INDIVIDUALIZED DIABETES TARGET BASED ON PATIENT CHARACTERISTICS - Azman, Nabilla Husna; Tan, Wen Hui; Zaharuddin, Noorhidayah; Nasir, Muhammad Ashraf Abd; Paidi, Norlizah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND The latest evidence showed setting a general HbA1c target for all patients is outdated. No published study in Malaysia investigates the patients’ achievement based on individualized diabetes targets. The study aims to focus on the impact of pharmacist-led diabetes education on patient achievement based on individualized HbA1c targets. CASE This retrospective cross-sectional study involved 306 patients who completed the Diabetes Medication Therapy Adherence Clinic (DMTAC) in 2020. They were conveniently sampled across 13 health clinics in Kota Tinggi district. Gestational diabetes mellitus patients and those under treatments that may affect the HbA1c level were excluded. Target HbA1c level was stratified according to the patient’s characteristics. Data obtained from electronic databases and medical reports were analysed using SPSS version 28.0.0. Descriptive analyses were utilized to compare differences in achievement between individualized and general HbA1c targets. Chi-square test of independence analysed the association between the HbA1c target group and age group with pre-stratified target achievement. More patients were able to achieve individualized HbA1c targets compared to the general HbA1c targets (25.5% vs 13.1%, respectively). A significant association was found between the HbA1c target group and target achievement (p <0.001) with the most achievable individualized HbA1c target group being 7.1-8% (43.9%). Age group and target achievement were found to be significantly associated when using individualized HbA1c targets (p <0.001), but not when using a general HbA1c target (p = 0.189). CONCLUSION An individualized HbA1c target gives better achievement compared to the general HbA1c target across diabetic patients under the DMTAC service. This suggests integrating individualized HbA1c targets in diabetes management.